PENGARUH MEDIA PEMBELAJARAN RODA BERPUTAR TERHADAP MINAT BELAJAR SISWA MATA PELAJARAN PPKN SDN 136 PALEMBANG - Juli Dwianty, Ranty; Ramanata Disurya; Mega Kusuma Putri (Study program PGSD FKIP Universitas Bung Hatta, 2024)
This study aims to determine the influence of Spinning Wheel learning media on Student Learning Interest in PPKn subjects SDN 136 Palembang. The research method used is quantitative type of experiment with the form of True Experimental Design design and Posttest Only Control Design research design. The population in this study amounted to 104 grade IV students and the sample in this study amounted to 52 students consisting of class IV C as a control class totaling 25 students and class IV D as an experimental class totaling 27 students with the technique used Simple Random Sampling. The data collection techniques used are Questionnaire (Questionnaire), Observation, and Documentation. The data analysis technique used is the t test (Independent Sample T Test). From the results of research data processing using the SPSS 26 application, t-count value = 5.622 and t-table value = 1.676 with ? = 0.05 and df = 50, thus t-count = 5.622 > t-table = 1.676. In accordance with the requirements of the hypothesis test, H0 is rejected and Ha is accepted or there is an influence of Spinning Wheel learning media on Student Learning Interest in PPKn subjects SDN 136 Palembang. Keywords: Learning Media, Spinning Wheel, Student Learning Interes